2007
DOI: 10.3923/pjbs.2007.2603.2605
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Mucilage Cells in Different Organs in Some Species of Malva, Althaea and Alcea

Abstract: Distribution of Mucilage Cells (MC) in leaves and petals of two species of Malva L. : Malva neglecta Wallr and M. nicaeensis All, one species of Altheae L.: A. officinalis L. and one species of Alcea L: A. angulata (Freyn and Sint.) Freyn and Sint. ex Iljin, have studied. Except ofA. angulata that mucilage cells observed both in epidermis and mesophyll of leaves, in the others mucilage cells confined to epidermis cells. All of species have mucilage cells in the petals. The area of the mucilaginous elements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The root of the Althaea officinalis plant has antitussive and pain relieving effects and is used in traditional medicine to decrease inflammation, chronic cough, angina, bronchitis (Bone, 1993;Mirhaidar, 2010). Althaea officinalis has effective ingredients such as flavonoids of the polyphenols group, polysaccharides, mucins, antocyanins, and fiber (Bradley, 1992;Razavi, 2003;Kardosova and Machova, 2006;Sutovska et al, 2007;Pakravan et al, 2007;ESCOP, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…The root of the Althaea officinalis plant has antitussive and pain relieving effects and is used in traditional medicine to decrease inflammation, chronic cough, angina, bronchitis (Bone, 1993;Mirhaidar, 2010). Althaea officinalis has effective ingredients such as flavonoids of the polyphenols group, polysaccharides, mucins, antocyanins, and fiber (Bradley, 1992;Razavi, 2003;Kardosova and Machova, 2006;Sutovska et al, 2007;Pakravan et al, 2007;ESCOP, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Total mucilage content (TMC) was measured both in the flowers and herbage of the examined taxa. Results showed that this parameter was under the influence of the genetic structure [20], geographical condition [21] as well as the organ of choice [20]. TMC was predominantly higher in the flowers as compared to the herbage of the taxa (Table 2).…”
Section: Total Mucilage Contentmentioning
confidence: 99%
“…The main factor that determines the quality of the marshmallow root as the drug is the amount of mucilage. According to Pakravan et al (2007), the structure and size of secretory tissue in Marshmallow's root correspond with the content and chemical composition of its active substances. In many medicinal plants genetic and environmental factors may influence the concentration of plant secondary compounds and active component in drugs, therefore the quality control is one of the major problems in the rational use of herbal medicines.…”
Section: Introductionmentioning
confidence: 99%